Women-Owned SMEs in Indonesia : A Golden Opportunity for Local Financial Institutions - International Finance Corporation (International Finance Corporation, Washington, DC, 2016)
Indonesia, a member of the G20 since 2008, has become one of the largest economies worldwide with the promise of substantial growth potential in the coming decades. In order to realize this potential, the government of Indonesia has identified the role of the Micro, small and medium enterprise sector as pivotal to promoting growth, creating jobs, and alleviating poverty. This joint International Finance Corporation (IFC) study on Women-Owned Small and Medium Enterprises (SMEs) in Indonesia makes a significant contribution in understanding women’s economic empowerment in the country by presenting a comprehensive analysis that captures original data. More than half of Indonesia’s SMEs are owned by women. And even though businesses run by women and men should in theory contribute equally to economic growth, the reality is that women face many more constraints in starting and growing their businesses, including obtaining business finance. This study intends to inform the government, private and state-owned banks, and the international community about the constraints faced by small businesses, particularly those owned by women. Additionally, the objective is to establish a business case for banks to help them realize the growth opportunity and contribute to their profitability by servicing this sector. It is clear from this report that significant reform will be necessary to improve both the business enabling environment for women and more importantly, to increase their access to finance. This book is arranged as follows : Following introduction, Chapter 2 provides an overview of the SME sector and summarizes the key findings about the enabling environment. Chapter 3 discusses access to finance, and the supply and demand of bank loans for SMEs and women-owned SMEs, Chapter 4 focuses on specific challenges, patterns of access, usage and demand for financial services by women-owned SMEs. Chapter 5 provides recommendations for the government, Bank Indonesia and banks in general, and Chapter 6 draws conclusions.